1981
DOI: 10.1111/j.1528-1157.1981.tb04334.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Seizure Frequency and Test‐Retest Scores on the Wechsler Adult Intelligence Scale

Abstract: Test-retest performance on the Wechsler Adult Intelligence Scale (WAIS) of two groups of adult epilepsy patients are presented and compared. In one group, Seizures Improved (SI) group, seizure frequency had decreased during the test-retest interval, and in the other group, Seizures Unimproved (SU) group, the number of seizures had either increased or stayed the same over the test-retest interval. The SI group showed a significant test-retest improvement on WAIS Verbal IQ, Performance IQ, and Full Scale IQ, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 23 publications
3
25
0
2
Order By: Relevance
“…In 1968 Rodin (17) reported intellectual decline in adults with poorly controlled seizures in contrast to improved intellectual functioning in patients who had experienced periods of remission ≥2 years in the intertest interval. Similarly, Seidenberg et al (18) reported intellectual gains in association with improved seizure control. Other investigators reported stable cognitive functioning in individuals with good seizure control (19)(20)(21) and, conversely, a poorer cognitive outcome in patients with continuing seizures (22,23).…”
mentioning
confidence: 87%
“…In 1968 Rodin (17) reported intellectual decline in adults with poorly controlled seizures in contrast to improved intellectual functioning in patients who had experienced periods of remission ≥2 years in the intertest interval. Similarly, Seidenberg et al (18) reported intellectual gains in association with improved seizure control. Other investigators reported stable cognitive functioning in individuals with good seizure control (19)(20)(21) and, conversely, a poorer cognitive outcome in patients with continuing seizures (22,23).…”
mentioning
confidence: 87%
“…In addition, interpretation of studies involving patients with epilepsy is often complicated because of changes occurring in other important variables suspected of influencing cognition such as seizure frequency (Seidenberg et al, 1981) and the withdrawal of alternative anti-convulsant medication (Thompson, in preparation). Considering the widespread use of sodium valproate in epilepsy it seems important to assess further its influence on cognitive functioning, in particular whether it does exert any beneficial effects as has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is a common sequel of encephalitis -roughly a quarter of the survivors suffering from it (McGrath, Anderson, Croxson, & Powell, 1997) -and seizures cannot always be controlled by medication. A high seizure frequency has been shown to have a detrimental effect on cognitive functioning (Dikmen & Matthews, 1977;Seidenberg, O'Leary, Berent, & Boll, 1981;Dodrill, 1986); memory performance in particular may deteriorate because of epilepsy-related neurone loss in the hippocampus (Mouritzen Dam, 1980). If this is the sole cause of progression, the problem may be alleviated with new developments in epilepsy medication.…”
Section: Global Cognitive Declinementioning
confidence: 98%